The Study of School Educational Environment in the Context of Ensuring Equal Access to Quality Education - E. V. Ivanova; I. A. Vinogradova; S. A. Zadadaev (Obrazovanie i Nauka, 2019)
Introduction. Today, official international and State Russian documents require ensuring equal access to quality education for all citizens regardless of place of residence and social status. In this regard, it becomes relevant to determine the quality of school environment and its potential in terms of compliance with the requirements of delivery of quality education services for all representatives of the oncoming generation.The aim of the present research is to study the educational environment of Moscow schools in the context of ensuring equal access to quality education.Methodology and research methods. An international assessment tool – the SACERS scale – was chosen as the main method of the research. The SACERS scale was modified by the employees of Laboratory of Educational Infrastructures of the Institute of System Projects of Moscow City University (MCU). The data were processed using descriptive statistics methods, dispersion and regression analysis, T-student’s criterion in the modification of Welch.Results and scientific novelty. On the basis of random sample (22 educational complexes), the peculiarities of educational conditions in different Moscow schools were diagnosed; the quality index of their educational environment and its structural components were determined (n = 58). The study sample revealed the “heterogeneity” of secondary educational establishments in the organisation of the subject-spatial environment of schools, extracurricular activities and additional education, as well as availability of educational infrastructure for students with special educational needs. Sufficiently equal indicators of educational conditions were identified: “Attendance”, “Space for Gross Motor Activities”, “Discipline”, “Peer Interactions”, “Interactions between Staff and Parents”, “Opportunities for Professional Growth”. Six “homogeneous” and ten “inhomogeneous” complexes were revealed in the studied sample. In “homogeneous” complexes, there are educational conditions, which provide relatively equal access to quality education, as compared with “heterogeneous” complexes. This fact is confirmed by the range of values of the quality index of the educational environment and the values of standard deviation.Practical significance. The present research allowed the authors to obtain a differentiated understanding of the existing educational conditions of Moscow schools, which formed the basis to solve the management problem in the development of education system, which guarantees quality education for all students.